PENGURANGAN GAS RUMAH KACA DARI LIMBAH CAIR DI PABRIK KELAPA SAWIT PT PERUSAHAAN NUSANTARA, RIAU - Febijanto, Irhan (BPPT)
Waste water utilization in palm oil mills (POMs) in Indonesia is limited only for land application and in some palm oil mills the waste water is unutilized and it is only discharged to a river. The technology of methane gas utilization produced from waste water have been developed, unfortunately economical barrier is a big problem to implement it in the POMs. Since Clean Development Mechanism (CDM) have been being introducing in Indonesia, many foreign investors who looking for Certified Emission Reduction (CER) visit and investigate potential reductions in Indonesia. Using CDM Mechanism, it will change feasibility of an activity of methane gas capture. An income from selling CER makes theeconomical feasibility of methane gas capture increase. The purpose of this study is to investigate the potential methane gas produced in waste water pond in all POM owned by PTPN V, located in Riau Province. Area of own plantation, amount of processed (Fresh Fruit Bunch (FFB) and distance of the location are proposed as a consideration for selecting candidate locations. The potentialmethane gas captured was calculated. It was known that four POMs have a potential methane gas amount produced from waste water pond, and the investment in those locations were feasible based on the NPV calculation result. Utilization of captured methane gas as a fuel for power generation is inconsiderate, because negotiation is predicted will be takes a long time.Key words: green house gasses, palm oil mill, empty fruit bunch, fresh fruit bunch, palm mill oil effluent, clean development mechanism